Relação dos motivos do encaminhamento de crianças para um Centro Especializado de Reabilitação Auditiva - Rezende, Julia de Araujo (2021)
Introduction: Neonatal hearing screening allows children with risk factors or who have failed the test to be referred for audiological diagnosis early. However, the literature points out that there are still a large number of children arriving late to diagnostic services. Objective: To analyze the relationships between reason for scheduling, age, time of diagnosis in a hearing health service. Method: The medical records of 276 children scheduled for audiological diagnosis at the SUS-accredited hearing health service in 2018 were analyzed. Results: Most children were boys - 58.3%. The average age of children on the first day of diagnosis was 19.8 months and the average number of times they attended audiological consultations was 2.8 times, with 27.2% not completing the diagnosis. Regarding the reason for scheduling, most children who started the diagnosis were babies who failed NHS (37.31%), followed by suspected hearing loss (26.08%), complaints related to language delay (23.18%) and risk factors (13.4%). Of the 201 children who completed the diagnosis, 55.72% had some level of hearing loss. The median age of children who completed the diagnosis with some degree and type of hearing loss is less than the median of children who completed the diagnosis without hearing loss. Conclusions: The group of children over the age of 16 months completed the audiological diagnosis in 30% more time than children younger than 16 months; most of the children in the age group greater than or equal to 16 months were diagnosed without loss; however, most children in the group under the age of 16 months were diagnosed with some degree of hearing loss. The study makes it possible to analyze the flow of scheduling children in the service so that a greater number of children can complete the audiological diagnosis and start the necessary intervention as soon as possible